Hydrophobic magnetic montmorillonite composite material for the efficient adsorption and microextraction of bisphenol A from water samples. Issue 4 (December 2016) - Salehinia, Shima; Ghoreishi, Sayed Mehdi; Maya, Fernando; Cerdà, Victor
Graphical abstract: Highlights: A hydrophobic magnetic montmorillonite composite was synthesized. The prepared sorbent was used for adsorption and extraction of bisphenol A. The kinetics, thermodynamics, isotherm and desorption condition were comprehensively studied. The prepared material was applied to the preconcentration of bisphenol A from water. Abstract: Herein we have synthesized a novel hydrophobic magnetic montmorillonite composite for the extraction of bisphenol A (BPA) from environmental water samples. The prepared sorbent is benefited by the advantages of eco-friendly montmorillonite, quick isolation of magnetic nanoparticles and hydrophobicity of C16 functional groups. The composite material was characterized by Fourier-transform infrared spectroscopy, x-ray diffraction and scanning electron microscopy. The thermodynamic and kinetic parameters of adsorption were studied by using direct fluorescence spectrophotometry. The kinetics and isotherm data can be well described by the pseudo-second-order kinetic model and the Langmuir isotherm, respectively. The maximum adsorption capacity (qm ) of hydrophobic magnetic montmorillonite for BPA obtained from a Langmuir isotherm was 59.17 mg/g at 298.15 K. The magnetic solid-phase extraction of bisphenol A was performed, and the analyte extracted was quantified using high performance liquid chromatography. Experimental parameters such as sorbent dosage, temperature, type and volume of desorption solvent, and adsorption and desorption time were evaluated. The linearity range of the method was between 0.5–200 μg L −1 with a determination coefficient (R 2 ) higher than 0.999. Relative standard deviations at two different concentration levels (50 and 200 μg L −1 ) were in the range of 2.4% and 1.8%, respectively. The limit of detection was 0.15 μg L −1 and the limit of quantitation 0.35 μg L −1 . Relative recoveries higher than 95% with RSDs in the range of 2.7–3.8% were achieved in the analysis of four different environmental water samples.